2015
DOI: 10.2224/sbp.2015.43.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Justice Climate and Job Performance: The Mediating Role of Industrial Relations Climate

Abstract: Drawing on the theories of social exchange and social information processing, we proposed and examined a multilevel model of distributive justice climate. Using hierarchical linear modeling and a sample of 1,618 employees of 49 companies in China, we found that distributive justice climate was positively related to industrial relations climate at the firm level. Furthermore, industrial relations climate mediated the relationship between distributive justice climate and employees' job performance. Our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Distributive justice also influences work outcomes (Liao & Rupp, 2005;Zhou & Li, 2015) by reducing turnover intention (Konovsky & Cropanzano, 1991) and by increasing satisfaction with employee compensation and benefits (Colquitt, Conlon, Wesson, Porter, & Ng, 2001). The perception of justice helps employees to feel more engaged with the company, thanks to an increased perception of organizational support from peers and supervisors (Biswas, Varma, & Ramaswami, 2013).…”
Section: H1 a Presenteeism Climate Is Positively Related To Wfcmentioning
confidence: 99%
“…Distributive justice also influences work outcomes (Liao & Rupp, 2005;Zhou & Li, 2015) by reducing turnover intention (Konovsky & Cropanzano, 1991) and by increasing satisfaction with employee compensation and benefits (Colquitt, Conlon, Wesson, Porter, & Ng, 2001). The perception of justice helps employees to feel more engaged with the company, thanks to an increased perception of organizational support from peers and supervisors (Biswas, Varma, & Ramaswami, 2013).…”
Section: H1 a Presenteeism Climate Is Positively Related To Wfcmentioning
confidence: 99%
“…The current study introduced high-quality relationships as the mediator of the distributive justice climate and virtual team performance. Previous studies have focused on industrial relations climate in traditional physical teams ( Zhou and Li, 2015 ), and this study opens the black box between the distributive justice climate and team performance in virtual teams from the perspective of social interaction, and thus, it is different from previous studies.…”
Section: Introductionmentioning
confidence: 78%
“…A distributive justice climate describes the common views of members on the fair distribution of organizational resources and rewards ( Whitman et al, 2012 ). Existing studies have found that a distributive justice climate exerts significant positive effects on team performance in traditional physical teams ( Lester et al, 2002 ; Lipponen and Wisse, 2010 ; Zhou and Li, 2015 ). Zhou and Li (2015) proposed that industrial relation climate mediates the relationship between the distributive justice climate and employees’ job performance, identifying the internal mechanisms of the effect of the distributive justice climate on job performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations